An action framework of incident command system (ICS) for Bangladesh armed forces in emergency response - Ullah, Md. Ashique Hasan (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2010.